1993
DOI: 10.1203/00006450-199311000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Inhibits Growth Hormone and Prolactin Secretion in the Human Newborn

Abstract: Dopamine is frequently used in neonatal intensive care for its vasopressor, renal vasodilating, and cardiac inotropic properties. The effect of i.v. dopamine infusion on neonatal pituitary hormone secretion is currently unknown. We observed strikingly low serum concentrations of growth hormone (GH) and prolactin (PRL) during a therapeutic, standardized, isovolumetric, partial exchange transfusion (blood sampling every 20 min for 6 h) in two polycythemic neonates requiring intensive therapy, including continuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
2
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 6 publications
4
53
2
1
Order By: Relevance
“…9,18 Although studies in the 1970s reported reductions in height in children treated with stimulant medication, 10,19 subsequent studies have been mixed, with some reporting growth reductions 16,[20][21][22] and others finding no significant growth changes. [23][24][25][26] Higher dosages of stimulants may cause more growth attenuation.…”
Section: Discussionmentioning
confidence: 99%
“…9,18 Although studies in the 1970s reported reductions in height in children treated with stimulant medication, 10,19 subsequent studies have been mixed, with some reporting growth reductions 16,[20][21][22] and others finding no significant growth changes. [23][24][25][26] Higher dosages of stimulants may cause more growth attenuation.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of supportive information regarding the use of therapies to increase BP, all of which are potentially toxic, 82,83 is a major concern. 84 In some NICUs, as many as 98% of the extremely low gestational age babies are exposed to these therapies.…”
Section: Discussionmentioning
confidence: 99%
“…High serum levels of GH and PRL (13) have been described during the first days of life (13)(14)(15). Values decrease afterward, but they are still high at 8 wk compared with adult concentrations (16).…”
mentioning
confidence: 97%